Assessment of Learning Styles of First-year Medical Students’ using VARK 8.02 Model Questionnaire: A Cross-sectional Study - Senthil Ganesh P Kannappan; Ravichandran Doraisamy; Vijayakumar Jagadesan (Journal of Clinical and Diagnostic Research)
Introduction: Students are constantly in search of additional and innovative ways to stimulate their attention in learning various subjects. Assessing medical students’ learning styles can help both teachers and students make informed decisions about teaching strategies. Adopting a suitable teaching style can improve teaching effectiveness. Fleming’s VARK Questionnaire version 8.02, which consists of V- Visual, A- Aural, R- Read/Write, and K- Kinaesthetic learning styles, was used in present study. Aim: To evaluate the learning styles of first-year MBBS students in a private medical college in Tamil Nadu India, identify the prevalence of unimodal and multimodal learners, and examine the correlation of learning styles between genders. Materials and Methods: A descriptive cross-sectional questionnaire survey was conducted among first-year MBBS students at Sri Venkateswaraa Medical College in Tamil Nadu, India from January 2024 to March 2024. A total of 125 students out of 150 provided their informed consent to participate in the research. Subsequently, a copy of the VARK questionnaire version 8.02, which contains 16 multiple-choice questions, was issued to the first-year MBBS students. To compare the learning styles of male and female students, Chi-square tests and paired sample t-tests were performed. Results: A total of 125 students participated in the present study. Participants’ age ranged from 18 to 22 years, with 37% being male and 63% female. Among the students, 38.4% were found to be unimodal, 46.4% were bimodal, 13.6% were trimodal, and 1.6% were quadrimodal learners. The individual scores in the unimodal category were V-3, A-14, R/W-5, and K-26, with kinaesthetic learning being the most preferred mode, followed by aural mode. There was no significant gender difference in the preferred learning style (p-value=0.35). The p-values for the association between learning styles and gender, determined through the Chi-square test in the unimodal category, were as follows: visual (p-value=0.93), aural (p-value=0.48), read/write (p-value=0.22), and kinaesthetic (p-value=0.18). Conclusion: Individual learning styles be identified at the entry level. Teachers can plan their lessons based on students’ learning preferences to improve the effectiveness and efficiency of their teaching and learning methods. To accommodate different learning styles, educators should combine various teaching methods.